STRATEGIES FOR THE MUHADHARAH COLLABORATIVE PROGRAM TO STRENGTHEN STUDENTS’ SELF-IDENTITY AT MTS AL-HUSNA PENUKAL - Saipul Anwar; Saipul Annur; Mardiah Astuti (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to describe and analyze the strategy of the Muhadharah Collaboration Program in strengthening students’ identity at MTs Al-Husna Penukal. The focus of the study includes program planning strategies, collaborative program implementation, and program evaluation in shaping students’ identity, which encompasses courage, self-confidence, discipline, responsibility, leadership, and the practice of Islamic values. The research employed a qualitative approach using a case study design. This approach was chosen to obtain an in-depth and contextual understanding of the implementation of the Muhadharah Collaboration Program in the madrasah environment. The research subjects consisted of the head of the madrasah, the vice head for student affairs, Islamic Education teachers, OSIS supervisors, and students. Data were collected through observation, interviews, and documentation. The data were analyzed using descriptive qualitative analysis and presented in narrative form. The results indicate that the strategy for developing the Muhadharah Collaboration Program at MTs Al-Husna Penukal was carried out in a planned, systematic, and collaborative manner involving various elements of the madrasah. The program was designed based on the needs of student character development and aligned with the vision and mission of the madrasah. The program implementation was conducted regularly and according to a structured schedule, with students actively involved as the main participants, while teachers and supervisors acted as facilitators and mentors. The program had a positive impact on strengthening students’ identity, as reflected in increased courage to speak in public, self-confidence, discipline, responsibility, cooperation, leadership, and the practice of Islamic values in daily life. Program evaluation was conducted periodically through reflection and joint deliberation, indicating that the Muhadharah Program is effective as a strategy for character building and strengthening students’ identity, although further improvements are still needed in technical aspects as well as facilities and collaboration with parents and the community.